Dispositional sexual motives as the mirror of values in heterosexual interpersonal relations - Igor A. Fourmanov (Национальный психологический журнал, 2017)
Background. Values of sexual relations repeatedly changed throughout various culturalhistorical periods. As a result of acquiring values and norms of sexual culture many actual requirements of the personthat were significant at certainontogenetic and sociogeneticstages couldget deprived of the relevance at further stages. As the sociocultural sexual development progresses the subsequent new values, highly significant for the given person are can be shaped. The system of values finds the reflexion in hierarchy and defines dynamics of sexual motives at different stages of the course of life. Objective. The objective is to define hierarchy, sexual and age distinctions in dispositional sexual motives in early adulthood. Design. The paper regards the issue of interrelation between sexual motivation and features of gender interpersonal relations. The sexual motivation was considered as interest in a general class of related incentives, all of which provide the same basic type of satisfaction associated with sexual expression. Eight specific types of incentives intrinsic to sexual expression that motivate sexual behaviourare studied: (1) feeling valued by the partner, (2) reinforcing partners value, (3) obtaining relief from stress or negative psychological states, (4) providing care and custody through sexual interaction to improve a partner’s psychological condition, (5) enhancing feelings of personal power, (6) feeling partner’s power, (7) feeling pleasure, and (8) productive fertility. Conclusion. Disregarding gender and age,the leading position in the hierarchy of sexual disposition motives is occupied by the motives of reinforcing partner’s value, pleasure and care, and subordination position, i.e. motives of comfort, personal value, power and submission. Females in comparison with males differ by higher intensity of submissionmotives and the partner’s significance, while males manifest more force of motive of production fertility. Within the years intensity of motives of partner’s significance, comfort, power and pleasure tends to increase, whereas the motives of submission, personal value and care tend to decrease. The motive of reproduction fertility does not change during years. Trends of al sexual disposition motivation in males and females at different stages of the early adulthood are designated.